2022
DOI: 10.3389/fendo.2022.806256
|View full text |Cite
|
Sign up to set email alerts
|

Increased Central and Peripheral Thyroid Resistance Indices During the First Half of Gestation Were Associated With Lowered Risk of Gestational Diabetes—Analyses Based on Huizhou Birth Cohort in South China

Abstract: ObjectivesThe study aimed to explore the relationship of thyroid function and resistance indices with subsequent risk of gestational diabetes (GDM).DesignThis was a longitudinal study embedded in the Huizhou Birth Cohort.MethodsA total of 2,927 women of singleton pregnancy were recruited from January to October of 2019. Thyroid central resistance indices were evaluated by Thyroid Feedback Quartile-Based index (TFQI), Thyrotrophy T4 Resistance Index (TT4RI), and TSH Index (TSHI) based on plasma-free thyroxine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
(77 reference statements)
2
19
2
Order By: Relevance
“…FT3 to FT4 ratio (FT3/FT4) can estimate the conversion efficiency of FT4 to FT3, which indirectly reflects the peripheral sensitivity of thyroid hormones. Increasing attention has been paid to the relationship between thyroid hormone sensitivity and metabolic disorders in recent years, and sensitivity to thyroid hormone indices have been proved to be reliable predictors of insulin resistance, type 2 diabetes (T2D), cardiometabolic risk, and disorders of glucose and lipid metabolism [20][21][22]. However, studies investigating the relationship between sensitivity to thyroid hormone indices and OA have not been reported.…”
Section: Open Accessmentioning
confidence: 99%
“…FT3 to FT4 ratio (FT3/FT4) can estimate the conversion efficiency of FT4 to FT3, which indirectly reflects the peripheral sensitivity of thyroid hormones. Increasing attention has been paid to the relationship between thyroid hormone sensitivity and metabolic disorders in recent years, and sensitivity to thyroid hormone indices have been proved to be reliable predictors of insulin resistance, type 2 diabetes (T2D), cardiometabolic risk, and disorders of glucose and lipid metabolism [20][21][22]. However, studies investigating the relationship between sensitivity to thyroid hormone indices and OA have not been reported.…”
Section: Open Accessmentioning
confidence: 99%
“…It is suggested that thyroid dysfunction may have a role in the emergence of GDM [ 4 , 5 ]. However, data are sparse on the association between different thyroid function markers and GDM based on the 2013 WHO criteria [ 12 , 13 ]. Data are also limited on the impact of thyroid function within the normal range on pregnancy outcomes and the risk of developing glucose intolerance in early postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Rawal et al showed that higher fT3 levels may be an indicator of GDM risk starting early into pregnancy [ 5 ]. A recent Chinese study showed that both peripheral and central thyroid resistance indices during the first half of pregnancy significantly affected the subsequent risk of GDM [ 13 ]. This study showed that higher levels of fT3 and a higher fT3-to-fT4 ratio were associated with increased GDM risk, even among euthyroid women [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations